2013
DOI: 10.1371/journal.pone.0075360
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for Distinctive Activation Patterns of Pain and Itchy in the Human Brain Cortex Measured Using Near Infrared Spectroscopy (NIRS)

Abstract: Pain and itch are closely related sensations, yet qualitatively quite distinct. Despite recent advances in brain imaging techniques, identifying the differences between pain and itch signals in the brain cortex is difficult due to continuous temporal and spatial changes in the signals. The high spatial resolution of positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) has substantially advanced research of pain and itch, but these are uncomfortable because of expensiveness, impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 37 publications
(43 reference statements)
1
49
0
Order By: Relevance
“…8 For example, Yücel et al 8 used innocuous and noxious electrical stimuli in 11 healthy subjects and obtained a localized hemodynamic response in the right and left motor-sensory regions; the noxious stimuli resulted in a higher response (HbO) as compared to the innocuous stimuli. In another study, Lee et al 15 observed distinct activation in the parietal and frontal areas for acute pressure pain and histamine-induced itch in seven subjects; the results showed a faster activation and stronger response of HbO signals for pressure pain than itch stimulation in both the frontal and parietal area. Ranger et al 16 recorded the HbO response of 20 critically ill infants (<12 months of age) during noxious procedures for cardiopulmonary bypass for various congenital heart defects (CHD) and found a significant bilateral increase in the somatosensory region despite the administration of analgesic treatment.…”
Section: Introductionmentioning
confidence: 91%
“…8 For example, Yücel et al 8 used innocuous and noxious electrical stimuli in 11 healthy subjects and obtained a localized hemodynamic response in the right and left motor-sensory regions; the noxious stimuli resulted in a higher response (HbO) as compared to the innocuous stimuli. In another study, Lee et al 15 observed distinct activation in the parietal and frontal areas for acute pressure pain and histamine-induced itch in seven subjects; the results showed a faster activation and stronger response of HbO signals for pressure pain than itch stimulation in both the frontal and parietal area. Ranger et al 16 recorded the HbO response of 20 critically ill infants (<12 months of age) during noxious procedures for cardiopulmonary bypass for various congenital heart defects (CHD) and found a significant bilateral increase in the somatosensory region despite the administration of analgesic treatment.…”
Section: Introductionmentioning
confidence: 91%
“…1 Similar relation has been reported between subjects' self-report and functional near-infrared spectroscopy (fNIRS) parameters. [2][3][4][5][6][7][8] For example, Lee et al 4 reported that as the intensity of the noxious pressure stimuli increases, the HbO 2 in the frontal cortex increases as well, consistent with an increase in the perceived pain.…”
Section: Introductionmentioning
confidence: 99%
“…As the frontal lobe is activated by pain or other unpleasant stimuli [68], we can support objective pain ratings according to a subjective declaration.…”
Section: Hemoencephalogram Recordingsmentioning
confidence: 99%
“…This measurement scheme provides a simple and convenient method for evaluating the dynamic responses of regional brain activities, which can be calculated from relative oxygenated hemoglobin and deoxyhemoglobin concentrations. As the frontal lobe is activated by pain or other unpleasant stimuli [68], we can support objective pain ratings according to a subjective declaration.…”
Section: Hemoencephalogram Recordingsmentioning
confidence: 99%